2012
DOI: 10.1001/archoto.2012.1753
|View full text |Cite
|
Sign up to set email alerts
|

Early Risk Factors for Enlargement of the Tracheoesophageal Puncture After Total Laryngectomy

Abstract: Objective To determine the early risk factors for enlargement of the tracheoesophageal puncture (TEP) after total laryngectomy. Design Retrospective cohort study. Setting The University of Texas MD Anderson Cancer Center, Houston. Patients The study included 194 patients who underwent total laryngectomy (with or without pharyngectomy) and TEP (2003-2008). Main Outcome Measures Multiple logistic regression methods were used to evaluate early risk factors for an enlarged TEP. Results The incidence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
1
1
1
Order By: Relevance
“…Likewise, the extent of surgery was not statistically predictive of device life. We agree that radiotherapy and extent of surgery are important factors that influence the success of TE voice restoration and postlaryngectomy functioning and have been described robustly in areas related to TE voice quality, swallowing, and postlaryngectomy complication . However, neither radiation nor extent of surgery showed any meaningful difference in device life in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Likewise, the extent of surgery was not statistically predictive of device life. We agree that radiotherapy and extent of surgery are important factors that influence the success of TE voice restoration and postlaryngectomy functioning and have been described robustly in areas related to TE voice quality, swallowing, and postlaryngectomy complication . However, neither radiation nor extent of surgery showed any meaningful difference in device life in this study.…”
Section: Discussionsupporting
confidence: 70%
“…We agree that radiotherapy and extent of surgery are important factors that influence the success of TE voice restoration and postlaryngectomy functioning and have been described robustly in areas related to TE voice quality, swallowing, and postlaryngectomy complication. [12][13][14] However, neither radiation nor extent of surgery showed any meaningful difference in device life in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…Few studies have looked at comorbidities as a risk factor for TEP com plication. Hutcheson et al 20 included Adult Comorbidity Evaluation-27 score, diabetes, TSH, albumin, alcohol use, and smoking status in their analysis of risk factors associ ated with TEP enlargement, but found that none of these factors were associated with this particular complication. Mehle et al 21 reviewed 146 secondary TEP procedures and found no increased risk of complication associated with alcoholism, diabetes, or COPD.…”
Section: Discussionmentioning
confidence: 99%